O gênero notícia de jornal em livros didáticos de língua portuguesa - Ana Karla de Carvalho Sousa (2010)
In this research, we have investigated the treatment given to the news in the newspaper of the Portuguese language textbooks for the third and fourth cycles of elementary school. We have examined the proposed reading of selected stories by authors of five collections for teaching 5th to 8th grade according to the approved National Program of Textbooks(PNLD/2008). We analyze the treatment given to this genre, investigating the nature of the activities presented in these collections and trying to assess whether the proposed reading contribute to achieving the goals set in the Portuguese National Curricular Parameters that focus this subject. The analysis of the corpus of this research is founded, primarily, on the assumptions of the bakhtinian theory of genres and authors of Text Linguistics. The characterization of the news is based on seminal studies such as Lage (1979, 2006), Miotto (2003), van Dijk (2002), Bonini (2002), and others, aiming at the production, reception and function of this genre in the journalistic field. According to the postulates of Schneuwly and Dolz (2004), we believe that genres in the school context become a communication tool, and the purpose of teaching and learning. The results indicate that the formal structure of the news and its language features in the activities suggested in the collections examined are prioritized over the discursive function of this genre. In this research, we have found that, in general, whether in greater or lesser extent, there is commitment of the authors of these collections in achieving the goals recommended by the Curricular Parameters for the teaching of ortuguese Language. The results also show that it is necessary to improve the proposed reading of the news so that such proposals could truly contribute to the formation of readers of that particular genre.